Family Interpersonal Communication in Overcoming Teenage Bullying Behavior in Medan City - Hardiyanto, Sigit; Adhani, Abrar; Lubis, Faizal Hamzah; Hidayat, Fadhil Pahlevi; Indainanto, Yofiendi Indah (Jogjakarta Communication Conference (JCC), 2025)
The emergence of the behavior of teenagers who experience character growth often shows negative behavior such as bullying. Based on data from the National Commission for Child Protection, the number of bullying cases among Indonesian teenagers is in fifth place out of 78 countries with the highest number of bullying cases. Efforts to eliminate this action by using family communication. The role of interpersonal communication in the family as a form of overcoming bullying behavior in adolescents. This research uses a qualitative descriptive method which aims to collect data related to family interpersonal communication, in this case carried out by parents in dealing with bullying behavior among teenagers in Medan City. The data collection technique in this research uses interview techniques with parents who have teenage children who are victims of random bullying, observation of activities carried out by parents with children in dealing with bullying behavior in children as well as documentation in the form of other supporting documents. The results of interpersonal communication research conducted by parents with teenagers in dealing with bullying behavior by communicating openly, honestly and being able to listen can prevent bullying behavior among teenagers. The role of the family must be to build communication between parents and children so that it runs smoothly, by actively listening and showing love and attention, so that the tendency of bullying behavior can be prevented and stopped by parents in the family.